Hemispherotomy for isolated infantile spasms following perinatal ischemic stroke. (September 2015) - Taussig, Delphine; Dorfmüller, Georg; Save, Jessica; Fohlen, Martine; Chipaux, Mathilde; Ferrand-Sorbets, Sarah; Delalande, Olivier; Bulteau, Christine
Abstract Background Infantile spasms (IS) are a severe epileptic encephalopathy. In patients with early focal ischemia and refractory IS, a preoperative evaluation is required even if IS are the only ictal manifestation. Methods We report three such patients who presented with IS between 5 and 7 months of age without any other focal seizure types. Imaging exhibited a perinatal middle cerebral artery (MCA) stroke. Results All patients had hemiparesis and experienced psychomotor regression after the onset of IS. Scalp video-electroencephalogram (EEG) monitoring for presurgical assessment showed interictal and ictal EEG characteristics between the pathological and the healthy hemisphere and surgery was proposed despite the lack of any focal seizures. The three patients underwent hemispherotomy at a mean age of 27 months and became seizure-free without medication (follow-up 49–144 months). The two patients who underwent early hemispherotomy acquired normal verbal intelligence, whereas the third, operated on at 38 months of age, remained with severe mental retardation. Conclusion Early hemispherotomy in drug-resistant epilepsy related to a perinatal MCA may cure the seizures even if the patient has IS as sole type and prevent mental retardation in some children.